Evolución histórica de los discursos médico-científico y religiosos sobre la mujer, la reproducción y la sexualidad - Esteban, Mari Luz (Estudios humanísticos. Geografía, historia y arte, 1994)
This article presents an overview of the evolution of the dominant conceptualizations of women, the female body, reproduction and sexuality as generated by the Medical-Scientific System and the Christian-Catholic Church, bringing a gendered perspective to the analysis. It also includes a look at what specialists (gynaecologists) believe and the influence they have on women.